2018
DOI: 10.3389/fmicb.2018.02558
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights Into the Cross-Feeding of Ruminococcus gnavus and Ruminococcus bromii on Host and Dietary Carbohydrates

Abstract: Dietary and host glycans shape the composition of the human gut microbiota with keystone carbohydrate-degrading species playing a critical role in maintaining the structure and function of gut microbial communities. Here, we focused on two major human gut symbionts, the mucin-degrader Ruminococcus gnavus ATCC 29149, and R. bromii L2-63, a keystone species for the degradation of resistant starch (RS) in human colon. Using anaerobic individual and co-cultures of R. bromii and R. gnavus grown on mucin or starch a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
115
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 45 publications
(72 reference statements)
1
115
1
2
Order By: Relevance
“…A similar pattern was observed for Lactobacillus in these categories as well, which further provided support of their mucin degrading capabilities. Interestingly, Ruminococcus also displayed this pattern in "carbohydrate transport and metabolism" and previous work have suggested that these are mucin degraders as well [40]. It is possible that these taxa may play important roles in foraging nitrogen from the host to the microbiome.…”
Section: Dynamics Of 15 N Incorporation Into Peptides Of the Mouse Gumentioning
confidence: 66%
“…A similar pattern was observed for Lactobacillus in these categories as well, which further provided support of their mucin degrading capabilities. Interestingly, Ruminococcus also displayed this pattern in "carbohydrate transport and metabolism" and previous work have suggested that these are mucin degraders as well [40]. It is possible that these taxa may play important roles in foraging nitrogen from the host to the microbiome.…”
Section: Dynamics Of 15 N Incorporation Into Peptides Of the Mouse Gumentioning
confidence: 66%
“…Interestingly, we found that the consumption of BB increases alpha diversity and modifies the gut microbiota by increasing the diversity of bacterial communities, mainly of the major phyla Gram-positive Firmicutes and of the class Clostridia of the genus Ruminococcus, mainly R. bromii, a key species for the degradation of resistant starch in the human colon [16], R. callidus and R. flavefaciens. From the genus Butyriciccocus B. pullicaecorum mainly increased, and from the genus Coprococcus, mainly C. eutactus, key species for the degradation of resistant starch in the human colon [25].…”
Section: Discussionmentioning
confidence: 92%
“…A possible explanation for these findings could be the changes in gut microbiota, mainly in butyrate-producing bacteria, as has been described [14,15]. Furthermore, one of the main components of beans is resistant starch, and, although there is considerable information on the effect of the different types of resistant starch on gut microbiota [16], few studies have focused on the effect of beans containing naturally resistant starch on the intestinal microbiota. One of the major sources of energy for microbial growth in the human colon is dietary resistant starch, which escapes digestion in the small intestine and reaches the colon undigested.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, another member of the Lachnospiraceae family, Ruminococcus , degrades intestinal mucins (similar in structure to EPS) liberating metabolites for other members of the microbiota to consume [36]. Thus, the positive correlation of Tyzzerella with formate in the EPS+ vessels suggests that, similar to other members in the Lachnospiraceae family, Tyzzerella may be consuming EPS and producing formate as a fermentation end-product [37]. Moreover, we observed several other strong negative correlations between different genus (e.g.…”
Section: Discussionmentioning
confidence: 99%